Reproduction and opportunity in talent development. A sports sociological study of Danish sportsclasses - Skrubbeltrang, L. Stausgaard (University Aalborg, 2018)
A growing focus on talent development in sports has led several countries, including Denmark, to adopt so-called dual-career initiatives to ensure that athletes are provided opportunities to pursue a career in sports while obtaining an education. Most research on dual-career initiatives has focused on athletes above the age of 15 who are enrolled in high school or university programs. Therefore, little is known about the consequences and effects of the programs aimed at younger athletes. Furthermore, because most research on talent development focuses on psychological or club cultural aspects of talent development, there is a lack of knowledge about the effects social background can have on talent development and dual career. In this article-based dissertation, I investigate Danish SportsClasses - a program aimed at athletes in 7th-9th grade (ages 13-15). The program is a collaboration between Team Danmark, the Danish Sports Association and local public schools. The published works of French sociologist Pierre Bourdieu inspire this dissertation`s theoretical framework. The aim is to investigate how talent is practiced in SportsClasses and the social implications of this approach. The dissertation is grounded in an ethnographic study of a Danish SportsClass (2013-2015) along with statistical analyses of two national surveys of all SportsClass students in Team Danmark-supported SportsClasses. In my analyses, I have focused on three aspects of the SportsClass program: 1) how students are selected for the program; 2) how students experience the SportsClasses and how their experiences are related to their social background, type of sport and gender; and 3) how the students construct their future aspirations in sports and education in relation to social background, type of sport and gender. These analyses led to three research products. In each of these products, I address one or more of these three aspects. My findings indicate that when investigating a talent development program such as SportsClasses from a sports sociological perspective, it becomes evident that `talent` is about more than a sport-specific skill set and that talent must be understood in relation to social structure. The findings from my three articles show that talent selection, students` experience of the SportsClasses and their constructions of aspirations in school and sports are closely related to social background and gender. Access to the SportsClasses is not entirely a question of sport-specific skills; it is also related to external factors, e.g., number of applicants and gender and type of sport distribution in the applicant pool. My studies also note an overrepresentation of students from middle and high socioeconomic backgrounds in the SportsClasses, despite intentions to create equal opportunities by placing SportsClasses in public schools. Findings from my studies suggest that the SportsClass initiative risks pushing toward an earlier specialization, despite most research in talent development advising against this approach. I found that 40% of boys and 60% of girls have been injured and experienced lack of motivation because of the increased hours of training in the program. My studies have shown that more attention should be given to female athletes because they are more likely to drop out of sports than are the male athletes. The career opportunities in sports are more limited for female athletes, which might explain why the girls in this study are more likely to focus on obtaining a degree. Finally, my studies have found that more students from the middle and upper-middle class are accepted into the SportsClasses, but that these students are less likely to aspire to a career in sports compared with students from a lower socioeconomic background. My overall findings suggest that social background and gender should be given much more attention than has most of the research on talent development done to date. Recognizing that talent development is about more than simply identifying the display of embodied capital but rather also reflects access to a broad variety of resources that have different values in different contexts could help in devising policies that succeed in creating opportunity for all applicants rather than reproduce social structures.